Language human rights and linguistic discrimination in European Union law
The topic of basic principles of the linguistic policy of the European Union, European law and the ECJ ’sjurisprudence on language rights of EU citizens and prevention of linguistic discrimination remain still unexploitedin scientific literature. The paper focuses on language rights of individuals in their relations withEU institutions in the case-study of recruitment processes. In the introduction the general, sociolinguisticcontext, related to the Language Human Rights movement and linguistic policy was taken into considerationwith regard to fundamental rights issues. Despite the specific, legal character of discourse and reasoning appliedin the paper, the conclusions presented on their grounds seem to be important for sociolinguistics sinceit is within i.a. this institutionalised communication that takes place a debate on the problems of languagesin contact, functioning of multilingualism, and some directives concerning linguistic communication thatinfluence its everyday realisations in UE .
Keywords: language human rights; linguistic discrimination; linguistic policy of the European Union; language and law